Analysis and proposal of improvements in the flow and control of red labels in a tpm line using industry 4.0 resources - Souza, Thiago Siqueira de; Carvalho, Flavio Lucio Santos de (Brazilian Journal of Production Engineering, 2022)
Based on industry 4.0 concepts, such as high intelligence capacity, increased productivity, the search for better efficiencies in processes and reducing costs, the article aims to analyze the long time taken to resolve red labels and propose, according to the concepts, improvements in the flow and control of red labels (ETVs) in the “A” production line of a food industry located in the city of Vila Velha - ES. For this, resources such as mobile technology, internet of things, big data and cloud computing were integrated into the flow and control in order to optimize the process, dealing with divergences in the label flow framework (QFET), eliminating wasted time in repairs, reducing the time for resolution of ETVs and contributing to the good of the environment with the proposal of the digital method. After analyzing the data, the results showed that red labels of priority B have the highest number of records, so it was necessary to analyze and propose improvements based on this type of label.